Transcriptional differences between major Fusarium pathogens of maize, Fusarium verticillioides and Fusarium graminearum with different optimum growth temperatures - Liu, Ning; Chen, Yue; Liu, Jing; Su, Qianfu; Zhao, Bin; Sun, Manli; Jia, Hui; Cao, Zhiyan; Dong, Jingao (Frontiers in Microbiology, 2022)
Fusarium verticillioides and Fusarium graminearum are important pathogens causing disease in maize (Zea mays) worldwide. The distributions of these fungal pathogens vary greatly in different regions and in different years, and are influenced by environmental and climatic conditions. Temperature has significant effects on the growth and mycotoxin production of Fusarium species. In this study, the effects of temperature on the growth and pathogenicity of F. verticillioides and F. graminearum were investigated. F. verticillioides grew fastest and exhibited the strongest pathogenicity to maize stems and grains at 30 °C , while F. graminearum grew best at 20 °C. Both species produced more toxins at 20 °C than at 30 °C. To explain the interspecific differences in the relationship of growth and temperature, RNA-seq was used to compare F. verticillioides and F. graminearum cultures cultivated for 4 d at the optimum temperatures of 30 °C and 20 °C, respectively. Samples of F. verticillioides were also cultivated for 9 d (to maximize toxin production) at 20 °C and 30 °C and analyzed by RNA-seq to investigate the influence of temperature for different growth stages. The differently expressed genes (DEGs) were identified by comparison of cultures grown for the same amount of time but at different temperatures. GO enrichment analysis showed high enrichment of DEGs in categories of membrane part, catalytic activity, metabolic process, and growth at warmer temperature resulted in more down-regulated DEGs enriched in membrane components in all groups. KEGG analysis revealed enrichment of DEGs related to different culture temperatures in carbohydrate and amino acid metabolism pathways. For both species, there was decreased expression of many DEGs related to amino acid metabolism when culturing at warm temperature, such as genes related to beta-alanine metabolism and arginine and proline metabolism. However, changes in genes related to glyoxylate and dicarboxylate metabolism and fatty acid degradation were more related to the growth state. The results showing different responses pattern of these pathways provides a foundation for further investigation of the molecular mechanisms underlying distinct thermal ecological niches of F. verticillioides and F. graminearum.